The effect of materiality (International Auditing Standard 320) in determining detection risks (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to explain how to determine audit risks, specifically detection risks, after determining the relative importance of financial statement items in accordance with International Auditing Standard 320. The research also aims to propose an audit program in light of International Auditing Standard 320. The research community represents general contracting companies because of its importance. And the impact on the economy of Iraq. As for the research sample, it represented the Hammurabi General Construction Contracting Company and analyzed the financial statements for the year 2021 by calculating relative importance and determining risks based on International Auditing Standard 320. One of the most important conclusions reached by the research was that there is an effect of applying the International Auditing Standard (320) Relative Importance. In determining discovery risks, one of the most important recommendations was the need for the external auditor to rely in determining discovery risks on the application of International Auditing Standard (320) Relative Importance.